If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2t+9=11
We move all terms to the left:
2t+9-(11)=0
We add all the numbers together, and all the variables
2t-2=0
We move all terms containing t to the left, all other terms to the right
2t=2
t=2/2
t=1
| 25^x+6=125^2x | | 4x-3(x+1)=0 | | g-4=47 | | -42-3u=8 | | 7=2u+5 | | 7/3y-49=0 | | 6x-3=13-2 | | n*3+15=45 | | (6y-15)+(15y+10)=73 | | f-4=-11 | | 44=b-50 | | 126-u=281 | | 19=6d-2 | | t/20=17 | | 2/5(x+3)=x-1 | | 9v=90 | | 0=8-5d | | 36÷=3y | | s+2=3.3 | | (3x^2)=400 | | 0=w/59+1 | | 0.25x=-0.64 | | y/2+17=30 | | R=(2x2x2)x100/64 | | -x^2=175 | | 2c2+18c+40=0 | | 35x+12=75 | | 9=w/4-12 | | 11=49z-3 | | 3s+1=34 | | x^2+2x+1+x^2=841 | | 2x=x-60 |